Explanation of the Ideal administrative system model from the perspective of Islam - Halimi Ali; Vatheq Qadir Ali (Kom: Časopis za Religijske Nauke)
Due to its importance and function in the development and well-being of societies as well as its irreplaceable role in solving the problems of administrative institutions, reducing social harms, including the reduction of administrative violence, the ideal administrative system has long attracted the attention of thinkers in the field of management, and so far, different models have been designed around it. One of these models is the ideal administrative system model from the perspective of Islam. Since the administrative system is influenced by the ideology that governs the political and administrative system of the governments, dealing with the model of the desirable administrative system needs to be planned and explained in line with the value system that governs societies and governments. Otherwise, the result of increasing violence, conflict and confusion in the field of action will not follow. By studying a number of Quranic stories and verses related to the life of divine prophets, thirteen Nahj al-Balaghah letters, verses and traditions related to the Age of Advent, and by using the inferential-interpretive method, present research explains the model of the ideal administrative system from the perspective of Islam, and from this channel in solving administrative system problems in Islamic countries. The general findings of the research show that the ideal Islamic administrative system has the seven elements of God, the Hereafter, people, law, justice, resources and sovereignty, a fair system based on love and equal service to human beings in human societies, regardless of religious and political differences. And, the race has been emphasized. The spirit of the ideal Islamic administrative system model is based on justice and love for human beings; this becomes possible when the human resources in the administrative system have distinct and different advantages in terms of belief and personality characteristics. Using the model of just and desirable Islamic administrative system in religious societies can significantly reduce the existing problems of administrative systems.